2021
DOI: 10.1038/s41598-021-99440-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phacoemulsification performed with vitrectomy on choroidal vascularity index in eyes with vitreomacular diseases

Abstract: This study evaluated the effects of cataract surgery combined with pars plana vitrectomy (ppV) on choroidal vascularity index (CVI) in eyes with epiretinal membrane (ERM) and full thickness macular hole (FTMH). Medical records of 132 eyes with ERM or FTMH were retrospectively reviewed and classified into a ppV group and a ppV combined with cataract surgery group (phaco + ppV group). The CVI were measured at baseline, 1, 3 and 6 months after the surgery, using the selected swept-source (SS) optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In addition, the reduced IOP is likely to cause increased CT in the early period following phacoemulsification performed with or without vitrectomy due to increased ocular perfusion pressure [ 21 , 22 ]. The present study demonstrated that the CT/CVI increased in the early postoperative period, which is similar to that reported in ERM and MH patients undergoing vitrectomy [ 21 , 23 ]. Therefore, the upregulation of proinflammatory cytokines and the decreased IOP after surgery might cause an increased CVI/CT after combined vitrectomy.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the reduced IOP is likely to cause increased CT in the early period following phacoemulsification performed with or without vitrectomy due to increased ocular perfusion pressure [ 21 , 22 ]. The present study demonstrated that the CT/CVI increased in the early postoperative period, which is similar to that reported in ERM and MH patients undergoing vitrectomy [ 21 , 23 ]. Therefore, the upregulation of proinflammatory cytokines and the decreased IOP after surgery might cause an increased CVI/CT after combined vitrectomy.…”
Section: Discussionsupporting
confidence: 91%
“…The CVI has proven to be informative in revealing the status of the choroidal vasculature in a variety of disease and treatment conditions [ 16 21 ]. The main objectives of this study were as follows: (1) to compare CVI in eyes with surgically resolved macula-off RRD treated with either primary vitrectomy alone or SB combined with vitrectomy; (2) to contribute to the analysis of submacular CVI as a marker; and (3) to create a multivariate linear model to identify potential correlations among final BCVA, age, CVI, the number of weeks with a detached macula, and the follow-up time after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Rizzo et al found that the CVI of eyes with ERM decreased at 1 and 3 months after vitrectomy [ 26 ]. Chun et al reported a long-term decrease in CVI in the PPV-alone group and a short-term increase in the PPV combined with cataract surgery group [ 27 ]. However, these studies analyzed CVI changes over a longer postoperative period.…”
Section: Discussionmentioning
confidence: 99%